Peningkatan Pemahaman Mengenai Larangan Rangkap Jabatan bagi Pengurus Lembaga Pemberdayaan Masyarakat Berdasarkan Peraturan Menteri Dalam Negeri Nomor 18 Tahun 2018 di Kecamatan Kulim - Eddy Asnawi; Andrizal; Birman Simamora; Alexsander Yandra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The partner problem is that many administrators of Community Empowerment Institutions in the Kulim sub-district do not yet know and understand the prohibition of concurrent positions for the management of Community Empowerment Institutions based on Minister of Home Affairs Regulation Number 18 of 2018 concerning Village Community Institutions and Village Traditional Institutions. The target of community service is to increase knowledge and understanding of Duties, Functions and Prohibitions for administrators. The output plans for this service activity are from drafts of scientific articles and mass media publications. The solution offered and agreed upon by the proposer and partners in overcoming the problem is that socialization needs to be conducted in legal counselling and discussion. The implementation method uses lectures and discussions. Lecturers deliver material, and participants are freed to have an interactive dialogue to obtain input in the form of problems, aspirations, proposals, ideas and solutions. Partners' participation in this activity is willing, provides time and place, and mobilizes the community as the target audience. The outputs that will be produced according to this community service activity plan are: for partners, of course, increasing knowledge and understanding of the duties, functions and prohibitions of management, for proposing the output to be achieved is in drafts of scientific articles.